A policy for the stimulated development of the Transkei - Gemmel, Robert (School of Architecture, Planning and Geomatics, 2020)
The aim of this study was to investigate the present development of the Transkei and to propose a policy for its future development, bearing in mind the potential of' the country and its people. The Transkei, an independent state, was looked at in relation to the developed areas of Southern Africa, and found to be geographically isolated from such economically developed areas and major communication links. Hence stimulated development is necessary. Physiographically the Transkei can be divided into three regions. Practically speaking two distinct regions can be distinguished, viz. the coastal sub-tropical region and the inland grass regions suitable for mixed farming.The natural resources which have the best development potential are forests, builders' marble, base minerals and water resources in general. Certain areas of the Transkei were found to be ideally suitable for the production of cash crops such as coffee, cotton, sugar, tea and fibre. The rest of the Transkei is suitable for mixed farming. There is thus a possibility of processing various products, i.e. an industrial potential. The problem in the Transkei is defined as basically a social problem; the attitude of the people does not create an environment conducive to economic development. Productivity per morgen and per person is low. With 98% of the population living in the non-urban areas and 85% of the economically active population being engaged in agriculture there is over-crowding on the land and per capita income is low.The standard of education of the people is low and there are virtually no employment opportunities other than in subsistence farming.